2007
DOI: 10.1002/ajh.21098
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter retrospective study defining the clinical and hematological manifestations of brucellosis and pancytopenia in a large series: Hematological malignancies, the unusual cause of pancytopenia in patients with brucellosis

Abstract: The aim of the study is to review the clinical manifestations and the hematological findings of brucellosis and pancytopenia, with or without hematological malignancies. The records of 202 patients with brucellosis were evaluated retrospectively. Among these cases of brucellosis seen in a 6 year period between April 1999 and June 2005, 30 patients with pancytopenia were identified. The most common manifestation was fever, followed by weight loss, anorexia, malaise, arthralgia, and hepatosplenomegaly. Bone marr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 24 publications
2
67
1
1
Order By: Relevance
“…11 Common hematological manifestations include leucopenia, anemia and thrombocytopenia. 12 The standard treatment for human brucellosis is doxycycline, 100mg BD and rifampicin 600-900mg once a day for 6 consecutive weeks. A combination of doxycycline and gentamycin is also preferred.…”
Section: Discussionmentioning
confidence: 99%
“…11 Common hematological manifestations include leucopenia, anemia and thrombocytopenia. 12 The standard treatment for human brucellosis is doxycycline, 100mg BD and rifampicin 600-900mg once a day for 6 consecutive weeks. A combination of doxycycline and gentamycin is also preferred.…”
Section: Discussionmentioning
confidence: 99%
“…Ocular manifestations include optic neuritis, papilledema and uveitis [19] . Common hematologic findings include leukopenia, anemia, and thrombocytopenia [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, studies have shown seropositive humans in Malaysia, mainly among veterinarians and farmers associated with occupational exposure to animals. The seroprevalent was mainly males (90%) within the age range between 20 and 45 years old [10] . This paper reports a case of human brucellosis involving a laboratory assistant in Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with malignant and pre-malignant hematological disorders living in endemic areas, brucellosis can cause: febrile illnesses; pancytopenia; systemic infections including endocarditis, meningoencephalitis, pulmonary insufficiency and splenic abscess; complicated bacteremia and serious morbidity [61,99,[106][107][108][109]150,151] Additionally, several cases of febrile neutropenia caused by infection with Brucella species have been reported in patients with malignant hematological disorders living in geographic locations that are endemic for brucellosis [147][148][149][152][153][154][155][156]. Brucellosis may develop at presentation of the hematological malignancy or even if the disease is under control [99,150,151].…”
Section: Brucellosis In Patients With Hematological Disordersmentioning
confidence: 99%
“…Hematological abnormalities in brucellosis include: leukopenia with relative lymphocytosis, neutropenia, anemia, thrombocytopenia, pancytopenia, DIC, microangiopathic hemolytic anemia (MAHA), hypersplenism, and elevation of ESR as well as CRP [1,61,189,190]. However, none of these hematological abnormalities is specific or characteristic for brucellosis [190].…”
Section: Hematological Abnormalities In Brucellosismentioning
confidence: 99%